The hate crime concept in GERMANY and how to improve the knowledge on the extent of hate crimes - Peucker, Mario ([Verlag nicht ermittelbar], 2006)
Contents: 1. Hate crime concept in the police registration system; 2. Weaknesses of the (new) police registration system; 3. A significant contribution: non-governmental victim support organisations; 4. Recommendation